Modular peptide binding interactions of sucker-ring teeth proteins - Hiew, Shu Hui (2017)
Biomimetics is highly integrated into our lives, inspiring us with ideas to advance technology and to design novel materials. The sucker ring teeth (SRT) of the Humboldt squid (Dosidicus gigas) is one such intriguing example, being a natural biotool that is both hard and strong, yet non-mineralized and fully proteinaceous (comprising of proteins named suckerins). With the aim of identifying the main building block of the SRT that endows the material with its mechanical strength, a bottom-up approach was undertaken to gain insight into the material’s design strategy and to obtain valuable molecular information.